Turmeric: Reemerging of a neglected Asian traditional remedy - Parviz Khajehdehi (Society of Diabetic Nephropathy Prevention, 2012)
Context: Turmeric (Curcuma longa) is a wild plant of the ginger family native to tropical South Asia. Evidence Acquisitions: Directory of Open Access Journals (DOAJ), Google Scholar, Pubmed (NLM), LISTA (EBSCO) and Web of Science have been searched. Results: Emerging evidence indicate that turmeric/curcumin inhibits cytokines and TGF-β production. From the various factors involved in the genesis of chronic kidney disease and pathogenesis of primary and secondary glomerulonehritis, TGF-β has emerged as a key factor in the cascade of events. Leading to glomerulosclerosis, tubulointerstitial fibrosis and end-stage renal disease. Conclusions: considering the inhibitory effect of turmeric/curcumin on cytokines and TGF-β, it seems wise to assume that supplementary turmeric/curcumin might be a candidate remedy for chronic kidney disease and possibly prevention of subsequent end stage renal disease.